2013
DOI: 10.1002/j.1556-6978.2013.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Moral Distress Within the Supervisory Relationship: Implications for Practice and Research

Abstract: Moral distress is the experience that follows when one feels constrained from acting according to what one believes to be ethically correct. A body of literature from counseling and other health‐related professions indicating the significant impact of morally distressing dynamics on individual and relational well‐being is presented, followed by implications for practice and future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…A study by Austin et al (2005), focusing on moral distress in psychiatric and mental healthcare settings, reported that psychologists described several incidents in which they felt their integrity had been compromised. Another study (Nuttgens and Chang, 2013) exploring moral distress within counseling supervisory relationships suggested that moral distress can result from supervisee vulnerability, substandard supervision, supervisee non-disclosure, and organizational pressures. Also in organizations, employees happen to manage situations where they observed inconsistencies between budget allocations and management responsibilities or where organizational priorities did not align with their personal values (Mitton et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Austin et al (2005), focusing on moral distress in psychiatric and mental healthcare settings, reported that psychologists described several incidents in which they felt their integrity had been compromised. Another study (Nuttgens and Chang, 2013) exploring moral distress within counseling supervisory relationships suggested that moral distress can result from supervisee vulnerability, substandard supervision, supervisee non-disclosure, and organizational pressures. Also in organizations, employees happen to manage situations where they observed inconsistencies between budget allocations and management responsibilities or where organizational priorities did not align with their personal values (Mitton et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…While the source is unclear, encouragement appeared to serve as a mediating factor for the self-care and success of students participating in field placement. Lazovsky and Shimoni (2007) and Nuttgens and Chang (2013) suggested encouragement, whether provided by the university or site supervisor, is a growthsupporting factor.…”
Section: Discussionmentioning
confidence: 99%
“…Just as research on MD has focused too narrowly on specific professions, it has also maintained a narrow scope on areas of practice. Thus, the area of psychiatry has largely been understudied in the context of MD (Austin, Bergum, & Goldberg, 2003;Deady & McCarthy, 2010;Nuttgens & Chang, 2013;Ohnishi et al, 2010). This being said, a (slowly) growing number of studies have been conducted in psychiatry in an attempt to identify the issues that give rise to the experience of MD, along with the barriers or constraints to action (Austin et al, 2005;Deady & McCarthy, 2010;Hamaideh, 2014;Musto & Schreiber, 2012).…”
Section: Mental Health and Moral Distressmentioning
confidence: 99%
“…This call for interventions has recently led three ethics journals 13 to devote full issues to the topic (Musto et al, 2015). Nevertheless, despite the growing interest in moral distress, few studies have been conducted in mental health care (Austin et al, 2003;Deady & McCarthy, 2010;Nuttgens & Chang, 2013;Ohnishi et al, 2010).…”
Section: Moral Distress Research In Mental Healthmentioning
confidence: 99%